2010
DOI: 10.1613/jair.2989
|View full text |Cite
|
Sign up to set email alerts
|

Narrative Planning: Balancing Plot and Character

Abstract: Narrative, and in particular storytelling, is an important part of the human experience. Consequently, computational systems that can reason about narrative can be more effective communicators, entertainers, educators, and trainers. One of the central challenges in computational narrative reasoning is narrative generation, the automated creation of meaningful event sequences. There are many factors -logical and aesthetic -that contribute to the success of a narrative artifact. Central to this success is its un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
274
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(277 citation statements)
references
References 58 publications
0
274
0
3
Order By: Relevance
“…have suggested that narrative text should be generated to represent each lifelog unit. As described by Riedl and Young (2010), "narrative is a sequence of events that describes how the story world change over time", and we know that narratives can be used to support keyword text searches using information retrieval techniques from Jaimes et al (2004). After all, text is the natural method that users now have to locate knowledge using web search engines.…”
Section: Making Use Of the Annotationsmentioning
confidence: 99%
“…have suggested that narrative text should be generated to represent each lifelog unit. As described by Riedl and Young (2010), "narrative is a sequence of events that describes how the story world change over time", and we know that narratives can be used to support keyword text searches using information retrieval techniques from Jaimes et al (2004). After all, text is the natural method that users now have to locate knowledge using web search engines.…”
Section: Making Use Of the Annotationsmentioning
confidence: 99%
“…With the exception of the systems mentioned above (see also [21]), most interactive storytelling systems do not directly address the emotional engagement of the audience. Rather, the research in interactive story generation tends to focus on the consistency of the plot in terms of characters' intentions and actions (see for example [13]). A notable exception is given by the use of player modeling to affect the emotional response of the users in [14].…”
Section: Emotional Systems In Interactive Storytellingmentioning
confidence: 99%
“…Narrative planning (Riedl & Young, 2010) is an application of planning in which the domain is a story world, the goal is the author's goal for the end state of the story, and the operators represent possible story events. For example, the domain might define an operator attack (?attacker*, ?victim, ?location).…”
Section: -The Indexter Modelmentioning
confidence: 99%